USAHATANI TANAMAN CAMPURAN DI KAMPUNG MANUMPITAENG KECAMATAN MANGANITU KABUPATEN KEPULAUAN SANGIHE - Misye N. Malemboris; Joachim N.K. Dumais; Juliana R. Mandei; Leonardus R. Rengkung (COCOS, 2014)
ABSTRACTMisye Nolanda Malemboris the income analysis of mix crop farming inManumpitaeng Village Manganitu Sub District, Sangihe Island RegencyUnder guidance of Jaochim N. K. Dumais as a chairman, Juliana R. Mandeiand Leonardus. R. Rengkung as members.The objective of this research is to know the mix of crop farming anddetermine farm in come mix plant the manumpitaeng village, manganitu subdistrict, Sangihe Island Regency.Data connected in this study is primary data and secondary data.Determining the sample of the research is conducted by purposive randomsampling which is based on a mixed crop farming that are already production.Sample used in this research is 9 people. Data in the study were analyzeddescriptively where the data collected is presented in tabular from and todetermine whether a mix crop farming is profitable or not by using R/C ratio farmin come mix plant, in village Manumpitaeng. Manganitu District, Sangihearchipelago district of the analysis return cost ratio (R/C) as a whole is greaterthan one that was 1,83 it means that the income earned in a single productionprocess is beneficial.